(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, in the process of education, elementary school students will develop their orthographic and orthographic knowledge by providing phonetic knowledge, and prepare the ground for independent completion of tasks using the knowledge acquired during the alphabet, mother tongue and reading literacy classes, innovative technology and exercises to achieve the desired results.